(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Relevance. Sports competitions are one of the most effective forms of organizing mass health-improving and sports work. Competitions act not only as a form, but also as a means of enhancing the general physical, sports-applied and sports training of students. Aim. This article is written about improving the pedagogical conditions for preparing students for sports competitions. Methods. In this article were used methods of analysis of scientific and methodological literature on the research topic; study of educational and normative documentation, state educational standard and curriculum; study of programs and curriculum - thematic plans, work experience of institutions of additional education; analysis of the results of the activities of teachers-trainers and students of the Faculty of Physical Education; ascertaining experiment; pedagogical observation; individual conversations with participants in the educational process; pedagogical experiment; mathematical and statistical methods of data processing, etc. Results. The types of competence, researches of scientists on the chosen topic are analyzed. Conclusion. Conclusions are given about the forms, methods and means for the improvement of pedagogical conditions for preparing students for sports competitions.